Posture Analysis of Musculoskeletal Complaints on Marble Creators in Bintang Indah Marmer, Tulungagung Regency - Ziana, Yusnia; Amarin Yudhana (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Musculoskeletal disorders are the second largest contributor to disabilities globally, with low back pain being the leading cause of global disability. The purpose of this study was to analyze the influence work posture for musculoceletal complaints on marble craftsmen at Bintang Indah Marmer, Tulungagung Regency. The design of this research is an observational quantitative study with a cross sectional approach with the focus of the research being directed to analyze the effectwork posture for musculoceletal complaints on marble craftsmen at Bintang Indah Marmer, Tulungagung Regencywith a population of 52 respondents and a sample of 46 respondents who were drawn using the simple random sampling technique. The findings show that hnearly half of the respondents have a body posture with a high risk category of 18 respondents (39.1%). Half of the respondents had musculoskeletal complaints in the moderate category, 23 respondents (50%). The results of the study used the test Linear Regression indicates that the p-value is 0.000 <0.05, then H1 is accepted, so it is concluded that there is the effect of work posture on musculoceletal complaints in marble craftsmen at CV. Bintang Indah Marmer Campurdarat, Tulungagung Regency, with a magnitude of influence of 81.4%. Workers when doing work to do work in a safe way, starting from adjusting body posture while working so as not to bend too much and more ergonomics, to reduce the risk of musculoskeletal complaints.